Power variation and time change - Barndorff-Nielsen, O; Shephard, N (Society for Industrial and Applied Mathematics, 2006)
This paper provides limit distribution results for power variation, that is, sums of powers of absolute increments under nonequidistant subdivisions of time and for certain types of time-changed Brownian motion and α-stable processes. Special cases of these processes are stochastic volatility models used extensively in financial econometrics.